A simple strategy to improve the interfacial activity of true Janus gold nanoparticles: a shorter hydrophilic capping ligand. Issue 1 (9th October 2015) - Fernandez-Rodriguez, Miguel Angel; Chen, Limei; Deming, Christopher P.; Rodriguez-Valverde, Miguel Angel; Chen, Shaowei; Cabrerizo-Vilchez, Miguel Angel; Hidalgo-Alvarez, Roque
Abstract : The use of a shorter hydrophilic capping ligand in true Janus nanoparticles leads to significantly improved interfacial activity. Abstract : Janus gold nanoparticles (JPs) of ∼4 nm-diameter half functionalized with 1-hexanethiol as a hydrophobic capping ligand exhibit significantly higher interfacial activity, reproducibility and rheological response when the other half is functionalized with 1, 2-mercaptopropanediol (JPs-MPD) than with 2-(2-mercaptoethoxy)ethanol (JPs-MEE), both acting as hydrophilic capping ligands. The interfacial pressure measured by pendant drop tensiometry reaches 50 mN m −1 and 35 mN m −1 for the JPs-MPD at the water/air and water/decane interface, respectively. At the same area per particle, the JPs-MEE reveal significantly lower interfacial pressure: 15 mN m −1 and 5 mN m −1 at the water/air and water/decane interface, respectively. Interfacial dilatational rheology measurements also show an elastic shell behaviour at higher compression states for JPs-MPD while the JPs-MEE present near-zero elasticity. The enhanced interfacial activity of JPs-MPD is explained in terms of chemical and hydration differences between the MPD and MEE ligands, where MPD has a shorter hydrocarbon chain and twice as many hydroxyl terminal groups as MEE.